Radioligand Binding to Quantify Adrenergic Receptor Expression in the Heart. Issue 1 (5th January 2023) - Grisanti, Laurel A.
Abstract: β‐adrenergic receptors regulate cardiac function in both the healthy and failing heart. Their expression is decreased in heart failure due to chronic overactivation of the sympathetic nervous system, contributing to declines in cardiac function and disease progression. Furthermore, therapies that prevent β‐adrenergic receptor downregulation or restore β‐adrenergic receptor levels are beneficial, making the determination of cardiac β‐adrenergic receptor expression in the heart an important consideration. Although quantitative RT‐PCR can provide an indication of β‐adrenergic receptor density and subtype expression, mRNA levels do not always correlate with functional protein levels. Additionally, antibodies to β‐adrenergic receptors lack specificity, making immunoblotting and other antibody‐based techniques unreliable. Radioligand binding assays were developed over 50 years ago and remain the gold standard for quantifying β‐adrenergic receptor densities in biological samples. This technique capitalizes on the binding of high‐affinity, highly specific ligands to receptors and can give quantifiable levels of receptor expression. Furthermore, competition assays using subtype‐selective antagonists generate binding profiles and can differentiate β‐adrenergic receptor subtype expression in cardiac tissue. This article focuses on the quantification of β‐adrenergic receptors in the heart using saturation and competition radioligand binding techniques to quantify β‐adrenergic receptor density and ligand affinities in cardiac membranes. © 2023 Wiley Periodicals LLC. Basic Protocol : Radioligand binding to quantify adrenergic receptor expression in the heart